T cell receptor repertoire characteristics both before and following immunotherapy correlate with clinical response in mesothelioma - Niek de Vries; Joachim G J V Aerts; Paul L Klarenbeek; Heleen Vroman; Giulia Balzaretti; Robert A Belderbos; Menno van Nimwegen; Koen Bezemer; Robin Cornelissen; Ilse T G Niewold; Barbera D van Schaik; Antione H van Kampen; et al. (Journal for ImmunoTherapy of Cancer)
Background Malignant pleural mesothelioma (MPM) is a highly lethal malignancy in need for new treatment options. Although immunotherapies have been shown to boost a tumor-specific immune response, not all patients respond and prognostic biomarkers are scarce. In this study, we determined the peripheral blood T cell receptor β (TCRβ) chain repertoire of nine MPM patients before and 5 weeks after the start of dendritic cell (DC)-based immunotherapy.Materials and methods We separately profiled PD1+ and PD1−CD4+ and CD8+ T cells, as well as Tregs and analyzed 70 000 TCRβ sequences per patient.Results Strikingly, limited TCRβ repertoire diversity and high average clone sizes in total CD3+ T cells before the start of immunotherapy were associated with a better clinical response. To explore the differences in TCRβ repertoire prior-DC-therapy and post-DC-therapy, for each patient the TCRβ clones present in the total CD3+ T cell fractions were classified into five categories, based on therapy-associated frequency changes: expanding, decreasing, stable, newly appearing and disappearing clones. Subsequently, the presence of these five groups of clones was analyzed in the individual sorted T cell fractions. DC-therapy primarily induced TCRβ repertoire changes in the PD1+CD4+ and PD1+CD8+ T cell fractions. In particular, in the PD1+CD8+ T cell subpopulation we found high frequencies of expanding, decreasing and newly appearing clones. Conversion from a PD1− to a PD1+ phenotype was significantly more frequent in CD8+ T cells than in CD4+ T cells. Hereby, the number of expanding PD1+CD8+ T cell clones—and not expanding PD1+CD4+ T cell clones following immunotherapy positively correlated with overall survival, progression-free survival and reduction of tumor volume.Conclusion We conclude that the clinical response to DC-mediated immunotherapy is dependent on both the pre-existing TCRβ repertoire of total CD3+ T cells and on therapy-induced changes, in particular expanding PD1+CD8+ T cell clones. Therefore, TCRβ repertoire profiling in sorted T cell subsets could serve as predictive biomarker for the selection of MPM patients that benefit from immunotherapy.Trial registration number NCT02395679.